2023
DOI: 10.3390/pr11020415
|View full text |Cite
|
Sign up to set email alerts
|

Toward the Transition of Agricultural Anaerobic Digesters into Multiproduct Biorefineries

Abstract: Anaerobic digestion allows for the proper management of agro-waste, including manure. Currently, more than 18,000 anaerobic digestion plants are under operation in EU, 80% of which are employed in the rural context. Tariff schemes for power generation from biogas produced during anaerobic digestion of agricultural feedstocks in Germany, Italy and Austria are coming to an end and new approaches are needed to exploit the existing infrastructures. Digesters in the rural context can be implemented and modified to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 38 publications
0
1
0
Order By: Relevance
“…Several economically sustainable techniques are available. A variety of demonstration plants has been established during the last years, and thus the establishment of industrial processes seems to be possible in the near future [ 131 136 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several economically sustainable techniques are available. A variety of demonstration plants has been established during the last years, and thus the establishment of industrial processes seems to be possible in the near future [ 131 136 ].…”
Section: Discussionmentioning
confidence: 99%
“…Validation of two theoretically derived equations for predicting pH in CO 2 biomethanisation [14] X X X Toward the transition of agricultural anaerobic digesters into multiproduct biorefineries [15] X X X…”
mentioning
confidence: 99%
“…As an approach with the explicit goal of making the best possible use of one unit of biomass, the concept of the biorefinery has evolved in the last decades; its main feature is to process biomass through different schemes operated widely in parallel, thus supplying a multitude of valuable outputs. Bolzonella et al [15] present a biorefinery pilot plant based on AD that was designed to supply a set of products, namely, energy products (hydrogen, methane), chemicals (short chain volatile fatty acids, polyhydroxyalkanoates), and other materials (nutrients for agriculture, microbial proteins for food or animal feed applications). In such a biorefinery, AD becomes one integrated element of a larger system, as it is complemented by other processes (mechanical, chemical, or biological).…”
mentioning
confidence: 99%
“…Both studies reported lower TAN recovery efficiencies of the removed TAN (55.3% and 54.45%,respectively). Therefore, it can be stated that more studies on nutrient recovery in digestates are necessary, since results may vary due to different feedstock characterizations for co-digestion (Bolzonella et al, 2023;Xie et al, 2018). In particular, it would be particularly relevant for agro-industrial waste that, due to their seasonality or their composition, there is no easy way to recycle them alone, such as apple pomace.…”
Section: The Ad Process and The Gpm Technology Tandemmentioning
confidence: 99%